2018
DOI: 10.1108/hff-11-2016-0473
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid atomistic-continuum multiscale method for fluid flow with density variation in microchannels

Abstract: Purpose This paper aims to extend the hybrid atomistic-continuum multiscale method developed by Vu et al. (2016) to study the gas flow problems in long microchannels involving density variations. Design/methodology/approach The simulation domain is decomposed into three regions: the bulk where the continuous Navier–Stokes and energy equations are solved, the neighbourhood of the wall simulated by molecular dynamics and the overlap region which connects the macroscopic variables (density, velocity and temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
(69 reference statements)
0
3
0
Order By: Relevance
“…Hybrid multi‐scale models offer a tractable alternative to purely atomistic or MD approaches, especially for more complex problems. For instance, hybrid methods using the concept of Geometric Decomposition of the solution domain, in which the continuum Navier–Stokes equations are solved in one region of the domain and atomistic molecular dynamics in another region, have been proposed by several researchers . The transport of microscopic and macroscopic information is done through an overlap region at the boundary of two adjacent regions.…”
Section: Introductionmentioning
confidence: 99%
“…Hybrid multi‐scale models offer a tractable alternative to purely atomistic or MD approaches, especially for more complex problems. For instance, hybrid methods using the concept of Geometric Decomposition of the solution domain, in which the continuum Navier–Stokes equations are solved in one region of the domain and atomistic molecular dynamics in another region, have been proposed by several researchers . The transport of microscopic and macroscopic information is done through an overlap region at the boundary of two adjacent regions.…”
Section: Introductionmentioning
confidence: 99%
“…There have been many studies for rarefied gas flows in nano/micro devices using direct simulation Monte Carlo (DSMC) and computational fluid dynamics (CFD) (Mizzi et al , 2007; White et al , 2013; Vu et al , 2018; Beskok, 2001; Shu et al , 2005; Zhou et al , 2017). The DSMC method can be used to solve the fluid dynamics problem for the entire rarefaction regimes (Bird, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…The hybrid atomistic-continual multiscale method was used in Vu et al (2018) for studies of gas flow in long microchannels subject to density variations. The authors demonstrated that this method enables effective computer simulations of large-scale problems with the accurate prediction of small-scale transmissions (slip velocity, temperature jump, thin condensation films etc.…”
Section: Introductionmentioning
confidence: 99%